PSFCS: Robust Emergency Communications Supporting High Mobility Based on WiMAX MMR Networks - Wen-Kang Jia; Chia-Yao Chen; Yaw-Chung Chen (International Journal of Distributed Sensor Networks)
Nowadays public safety networks are widely deployed to support highly reliable wireless communications in case of emergency. The adoption of standardized systems such as WiMAX for emergency communications represents a significant advance in the off-the-shelf technologies for error detection and error correction. Since it is difficult to fully eliminate the Doppler effect under high speed moving environment, we propose an enhanced CRC-based error correction scheme that carries as much extra segmented frame Check Sequence (FCS) information as subblocks of emergency multicast/broadcast service (MBS) frame, called progressive and selective frame check sequence (PSFCS). In a mobile multihop relay (MMR) environment, a high-mobility mobile station might receive an emergency MBS frame more than once, so the PSFCS could be cross-referenced by duplicated frames received. Therefore the PSFCS achieves a significant performance improvement over the legacy FCS scheme in terms of error detection and correction of emergency MBS frames in a WiMAX MMR network operating in transparent mode. The experimental results show that the goodput and utilization of high-mobility mobile stations can be improved remarkably.